Applying a relational lens to ethnographic inquiry: Storied insight into the inner workings of multicultural teams in men's elite football. (May 2021) - Darpatova-Hruzewicz, Donka; Book, Robert T.
Abstract: Objective: To examine the impact of transnational migration on the functioning of multicultural teams in men's elite football and to explore the cultural transition experiences of transnational players from the relational perspective of receiving football environments. Design: and Method: This 26-month ethnographic study adopted a researcher-practitioner approach to investigate two elite European football clubs during the course of two complete seasons. Over 80 male participants from 18 different countries were involved in the approximately 1200 h of field observation (e.g., practices, games, closed-door meetings, etc.) and 50 h of transcribed interviews. Detailed field notes and interview data were thematically analyzed, followed by a narrative analysis of structure and form. Finally, the genre of ethnographic creative non-fiction was employed to present the findings. Findings: By applying a relational lens to the study of cultural transitions, this investigation illuminates the centrality of relations in the daily functioning of multicultural teams embedded in transnational networks and spaces. The complex interactional dynamic between transnational players and members of the receiving environment as well as the structural constraints shaping footballing (sub)cultures and behaviours highlight the salience of restrained agency as a collective phenomenon in elite men's football. Moreover, the study explores the hows of cultural transition by engaging with temporality and proposing a complementary perspective that extends current understandings in the narration of cultural transition experiences. Conclusions: The findings carry applied utility that can benefit stakeholders and practitioners working with culturally diverse teams in the deployment of culturally informed club management strategy, educational tools, and interventions. Highlights: Findings are based on a two-year ethnographic study and presented in storied form as creative non-fiction. Relations are central to the daily management of multicultural teams in elite sport. Constrained agency as a collective phenomenon in football is embedded in relational matrices and emerges in transnational spaces. Novel insights on transition are generated through the exploration of receiving environments (coaches, directors and home-grown players). A phenomenologically driven view on temporality is offered as complementary to current understandings of cultural transitions in sport.